Lessons learned for surveillance system strengthening through capacity building and partnership engagement in post-Ebola Guinea, 2015-2019 - Jennifer J. Hemingway-Foday; Boubacar Ibrahima Diallo; Salomon Compaore; Souleymane Bah; Sakoba Keita; Ibrahima Telly Diallo; Lise D. Martel; Claire J. Standley; Mariama B. Bah; Marlyatou Bah; Djiguiba Camara; Almamy K. Kaba; et al. (Frontiers Media S.A., 2022)
The 2014-2016 Ebola outbreak in Guinea revealed systematic weaknesses in the existing disease surveillance system, which contributed to delayed detection, underreporting of cases, widespread transmission in Guinea and cross-border transmission to neighboring Sierra Leone and Liberia, leading to the largest Ebola epidemic ever recorded. Efforts to understand the epidemic's scale and distribution were hindered by problems with data completeness, accuracy, and reliability. In 2017, recognizing the importance and usefulness of surveillance data in making evidence-based decisions for the control of epidemic-prone diseases, the Guinean Ministry of Health (MoH) included surveillance strengthening as a priority activity in their post-Ebola transition plan and requested the support of partners to attain its objectives. The U.S. Centers for Disease Control and Prevention (US CDC) and four of its implementing partners-International Medical Corps, the International Organization for Migration, RTI International, and the World Health Organization-worked in collaboration with the Government of Guinea to strengthen the country's surveillance capacity, in alignment with the Global Health Security Agenda and International Health Regulations 2005 objectives for surveillance and reporting. This paper describes the main surveillance activities supported by US CDC and its partners between 2015 and 2019 and provides information on the strategies used and the impact of activities. It also discusses lessons learned for building sustainable capacity and infrastructure for disease surveillance and reporting in similar resource-limited settings.